Effect of radiotherapy on cardiac-specific death in patients with non-malignant tumors of central nervous system and related clinical features - Wang, Ruxin; Ye, Haowen; Zhao, Yongting; Ma, Li; Wei, Jinjing; Wang, Ying; Zhang, Xiaofang; Wang, Lihong (Frontiers in Cardiovascular Medicine, 2022)
Importance Cardiac-specific death from radiation caused by radiation therapy (RT) in patients with malignant tumors has received extensive attention, however, little is known regarding the potential cardiotoxic effects of RT in patients with non-malignant tumors. Objectives and Methods In this study, we used the SEER data to explore the incidence of post-radiation cardiovascular complications in patients with non-malignant tumors of central nervous system (CNS), and identify the influencing factors of cardiac-specific death. Results Ultimately 233, 306 patients were included (97.8% of patients had brain tumors and 2.2% had spinal cord tumors). For patients with non-malignant tumors of CNS, RT yes (odds ratio [OR] 0.851, 95% confidence interval [CI] 0.774-0.936, p=0.001, before propensity score matching (PSM); OR 0.792, 95% CI 0.702-0.894, p<0.001, after PSM) vs. no was associated with lower risk of cardiac-specific death, other clinical features affecting cardiac death similar to those in patients with non-malignant tumors of CNS receiving RT. For patients with non-malignant tumors of CNS receiving RT, female, married status, Hispanic ethnicity, surgery, and tumor site (brain exclude nerve and endocrine, nervous system) were associated with lower risks of cardiac-specific death, while earlier year of diagnosis, older age of diagnosis, Black, larger tumor and bilateral tumor were risk factors for cardiac-specific death. Conclusions This study shows the influencing factors for cardiac-specific death in patients with non-malignant tumors of CNS, and found RT is associated with lower risk of cardiac-specific death, which indicates that the effect of radiation on the heart depends on the biological behavior of tumor. These results can facilitate the identification of patients with non-malignant tumors of CNS who can benefit from RT while avoiding cardiovascular events and enhance the clinical use of RT in these populations, especially in patients who may have impaired cardiac function due to CNS tumors.